A MIOCENE ACERATHERIINE RHINOCEROTID (MAMMALIA, PERISSODACTYLA) FROM EARLY PLEISTOCENE MARINE DEPOSITS AT MONTE DELLE PICHE (ROME, CENTRAL ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
A fragmentary hemi-mandible of a rhinocerotid was collected during the end of the 19th century at Monte delle Piche (Rome). Morphological features, such as a short paralophid in the molar, the presence of a mesio-lingual cingulum in the teeth and a well-developed upturned I/2, indicate that the specimen is an Aceratheriinae. In addition to other taxa (e.g. Chilotherium, Aceratherium and Hoploaceratherium ), the hemi-mandible shows morphological traits suggestive of the genus Acerorhinus . The latter is well-documented in fossiliferous localities of South-eastern Europe, Turkey and China, chronologically related with the Land Mammal Zones MN 9-12. Unfortunately, the specimen is reworked in Early Pleistocene marine deposits.Hence, it cannot indicate the time at whichthe genus reached Italy.